A Comparative Study of Plantar Arch Index, Weight Distribution, Equilibrium Performance, and Selected Musculoskeletal Disorders in Active and Non-active Adolescences - Ali Fattahi; Haniyeh Zehtab Asghari; Zahra Koreili (Biyumikānīk-i varzishī, 2020)
Objective: musculoskeletal disorders cause the loss of beauty and decrease the mechanical performance of individuals. The functions of the steps on the floor are the attraction and distribution of forces and the provision of the body’s stability. The study aimed to compare arch index, weight distribution, balance, and selected musculoskeletal disorders in active and non-active adolescents. Methods: The sample consisted of 50 teenagers (28 active and 22 no actives) who were randomly targeted. The subjects demographics included the non-active adolescence with Mean±SD of Age: 12.46±1.10, Mean±SD of Height: 157.69±8.48 cm, and Mean±SD of Weight: 46.65±8.45; the active group with Mean±SD of Age: 12.26±1.13, Mean±SD of Height: 153.91±10.09, and with Mean±SD of Weight: 44.52±7.76. For statistical analysis of data, K-S test for normal distribution of data and used t-test to compare the two groups of active and non-active and U Mann–Whitney at the significance level of 0.05. Results: The descriptive findings indicate that the mean musculoskeletal system in adolescences is more active than active. The independent t-test for comparing the balance performance among the active and non-active groups showed a significant correlation (P=0.04). Still, there was no significant difference in the foot index parameters and weight distribution. Conclusion: Musculoskeletal diseases play a critical role in the mechanical function of individuals. The posture and balance performance in the active group was better than in non-active adolescences. Still, no difference was observed between the foot index and weight distribution in active and non-active juveniles. More complex research is needed to test this hypothesis.